ER–Mitochondria Microdomains in Cardiac Ischemia–Reperfusion Injury: A Fresh Perspective - Zhou, Hao; Wang, Shuyi; Hu, Shunying; Chen, Yundai; Ren, Jun (Frontiers in Physiology, 2018)
The mitochondrial and endoplasmic reticulum (ER) homeostasis is pivotal to the maintenance of an array of physiological processes. The physical contact and association between ER and mitochondria, known as the ER-mitochondria microdomains or mitochondria-associated ER membrane (MAM), temporally and spatially regulates the mitochondria/ER structure and function. More evidence suggests a role for MAMs in energy production, cellular contraction and mobility, and normal extracellular signal transmission. In pathological states, such as cardiac ischemia reperfusion (I/R injury), this ER-mitochondria microdomains may act to participate in the cellular redox imbalance, ER stress, mitochondrial injury, energy deletion and programmed cell death. From a therapeutic perspective, a better understanding of the cellular and molecular mechanisms of the pathogenic ER-mitochondria contact should help to identify potential therapeutic target for cardiac I/R injury and other cardiovascular diseases and also pave the road to new treatment modalities pertinent for the treatment of reperfusion damage in clinical practice. This review will mainly focus on the possible signaling pathways involved in the regulation of the ER-mitochondria contact. In particular, we will summarize the downstream signaling modalities influenced by ER-mitochondria microdomains, for example, mitochondrial fission, mitophagy, calcium balance, oxidative stress and programmed cell death in details.